2021
DOI: 10.2217/fon-2020-1266
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Symptoms, Disease Burden, Resource Use and Quality of Life in US Patients with Advanced Renal Cell Cancer

Abstract: Aim: To assess symptoms, healthcare resource utilization and health-related quality of life in advanced renal cell carcinoma (aRCC) clinical practice. Materials & methods: The USA point-in-time survey of physicians and patients was conducted between February and September 2019. Results: Data were available for 227 patients. Mean (standard deviation) number of symptoms was 3.4 (3.2); differences were observed across International Metastatic RCC Database Consortium risk categories (p < 0.001), with fewer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Few studies have been published detailing HCRU among patients with mRCC in LOT1. One study used the US point-in-time survey and reported a mean of 0.2 hospitalizations over the past 6 months in patients treated with IO-IO combinations. We observed a similar mean unadjusted PPPM for IP stays of 0.2 in the I+N group for the full follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been published detailing HCRU among patients with mRCC in LOT1. One study used the US point-in-time survey and reported a mean of 0.2 hospitalizations over the past 6 months in patients treated with IO-IO combinations. We observed a similar mean unadjusted PPPM for IP stays of 0.2 in the I+N group for the full follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the IMDC risk category could not be defined for 11% of the patients, while a previous RWE study conducted in the United States could not define the risk category for 40% of the patients. 12 RWE studies in the UK 13 and Norway 14 have highlighted improvements in the OS of aRCC patients with the introduction of targeted therapies. However, the absence of established prognostic factors, such as the IMDC risk category, in RWE studies does not provide details on OS according to risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Hall et al reported no association of IMDC risk category with hospitalization frequency – although their window of a 6-month data capture prior to treatment start may have affected this result. 12 …”
Section: Discussionmentioning
confidence: 99%
“…However, when the cancer progresses and becomes metastatic, the median survival drops to 55.7 months [ 6 ]. Tumor progression and metastasis have a strong impact on patient survival and the quality of life of kidney cancer patients [ 7 , 8 ]. The mechanisms by which tumors grow and disseminate in the body are not completely elucidated, but large extracellular vesicles (lEVs) may play a key role.…”
Section: Introductionmentioning
confidence: 99%